Chronic Liver Diseases and COVID-19: Database of General Hospital - E. Yu. Sitnikova; L. Yu. Ilchenko; I. G. Fedorov; I. G. Nikitin (SINAPS LLC, 2023)
Patients with chronic liver diseases (CLD) are at high risk of infection and severe COVID-19 (Corona Virus Disease).Aim: to create a database of patients with CLD, including an analysis of the frequency of detection of SARS-CoV-2 markers, the causes of hospitalization, an assessment of 30-day mortality in the presence of COVID-19 markers and in the absence of infection.Materials and methods. A one-time retrospective observational comparative study was conducted, the result of which was the creation of a database. 693 electronic case hystories of patients with CLD of various etiologies hospitalized in the V.M. Buyanov State Clinical Hospital for the period 01.04.2020-01.10.2021 were analyzed. Th e analysis included the following parameters: gender, age, etiology of the disease, reasons for hospitalization, the presence of ribonucleic acid (RNA) SARS-CoV-2 in a smear of the nasal mucosa and oropharynx, antibodies to SARS-CoV-2 immunoglobulins of classes M, G (IgM, IgG), the outcome of the disease (30-day mortality).Results. Markers of past new coronavirus infection (IgG) were detected in 268 (38,7 %), SARS-CoV-2 RNA was detected in 67 (9,7 %). Th e analysis of the causes of hospitalization revealed the predominance of edematous ascitic syndrome (64,5 %), an increase in hepatic encephalopathy (31,6 %) and an increase in the number of cases of portal vein thrombosis (PVT) (8,9 %). When assessing the 30-day mortality, signifi cant diff erences were found in patients with Alcohol-related liver disease (ARLD), chronic viral hepatitis in the presence of COVID-19 markers and in cases of their absence.Conclusion. SARSCoV-2 markers were found in 335 (48,3 %) of patients with CLD. Th e main reason for hospitalization is the appearance /increase of edematous ascitic syndrome, including due to PVT. 30-day mortality in the postcovid period is signifi cantly higher (р = 0,0246) in ARLD compared with patients without COVID-19 (218 (34,9 %) и 300 (25,3 %), respectively, р = 0,0246).